10. Famous Pianists Perform Beethoven 32 Variations on an Original Theme in C Minor According to the Pianists Daniel Barenboim and Evgeny Kissin - Tudor Brîndușa (Sciendo, 2021)
Year 2020 constitutes an incredibly significant landmark in the classical music history as it is the year celebrating 250 years since the composer Ludwig van Beethoven was born. The "32 Variations on an Original Theme in C minor" are deemed to be some of the most brilliant pianistic works marking the second period of Beethoven creation. The interpretative visions of Daniel Barenboim and Evgeny Kissin are equally interesting, the two great pianists putting their personality, sensitivity, and culture mark. All these elements confer upon the piece "32 Variations on an Original Theme in C minor" particular expressive valences highlighting Beethoven's creative genius.